Ghana's energy access journey so far: a review of key strategies. Issue 1 (2nd September 2020) - Bukari, Dramani; Tuokuu, Francis Xavier Dery; Suleman, Shafic; Ackah, Ishmael; Apenu, Godwin
Abstract : Purpose: The purpose of this paper is to present a comprehensive review of the programmes being implemented with a view to ascertaining if they adequately address the energy needs of the poor more holistically and sustainably. Design/methodology/approach: The content of this desktop review is based on information collected through a review of available energy policy documents from the Ghana Government and related governmental agencies, such as the Energy Commission and Ghana Statistical Services, international energy-related agencies, such as the International Energy Agency (World Vision, 2013), as well as other related web searches. Additionally, global and Sub-Saharan African energy access documents were reviewed by analysing secondary data from the World Bank and UN policy reports, statistical data, strategies, regulations, protocols and other related documents (World Vision, 2013). Furthermore, some policy documents on energy access and usage were explored mainly from Senegal and Ghana to ascertain governments' policies, regulations and strategies in the implementation of energy access policies. Findings: The paper offers all the various strategies being implemented in an attempt to establish a foothold on the problem of affording the poor with clean and affordable energies. The paper also presents the rich experiences of Senegal in its bid to see expanded access in liquefied petroleum gas usage by residential consumers. Originality/value: The paper provides some policy and theoretical implications for improving Ghana's energy access.